Serum concentration impacts myosin heavy chain expression but not cellular respiration in human LHCN‐M2 myoblasts undergoing differentiation. Issue 2 (9th January 2023) - Turner, Mark C.; Brett, Ryan; Saini, Amarjit; Stewart, Claire E.; Renshaw, Derek
Abstract : New Findings: What is the central question of this study? Does the concentration of human serum affect skeletal muscle differentiation and cellular respiration of LHCN‐M2 myoblasts? What is the main finding and its importance? The concentration of serum used to differentiate LHCN‐M2 skeletal muscle cells impacts the coverage of myosin heavy chain, a marker of terminally differentiated myotubes. Normalisation of mitochondrial function data to total protein negates the differences observed in absolute values, which differ as a result of increased protein content when differentiation occurs with increasing concentration of serum. Abstract: The human LHCN‐M2 myoblast cell line has the potential to be used to investigate skeletal muscle development and metabolism. Experiments were performed to determine how different concentrations of human serum affect myogenic differentiation and mitochondrial function of LHCN‐M2 cells. LHCN‐M2 myoblasts were differentiated in serum‐free medium, 0.5% or 2% human serum for 5 and 10 days. Myotube formation was assessed by immunofluorescence staining of myosin heavy chain (MHC) and molecularly by mRNA expression of Myogenic differentiation 1 ( MYOD1 ) and Myoregulatory factor 5 ( MYF5 ). Following differentiation, mitochondrial function was assessed to establish the impact of serum concentration on mitochondrial function. Time in differentiation increased mRNA expression of MYOD1 (day 5, 6.58 ± 1.33‐fold; and day 10, 4.28 ± 1.71‐fold) ( P = 0.012), while suppressing the expression of MYF5 (day 5, 0.21 ± 0.11‐fold; and day 10, 0.06 ± 0.03‐fold) ( P = 0.001), regardless of the serum concentration. Higher serum concentrations increased MHC area (serum free, 11.92 ± 0.85%; 0.5%, 23.10 ± 5.82%; 2%, 43.94 ± 8.92%) ( P = 0.001). Absolute basal respiration approached significance ( P = 0.06) with significant differences in baseline oxygen consumption rate ( P = 0.025) and proton leak ( P = 0.006) when differentiated in 2% human serum, but these were not different between conditions when normalised to total protein. Our findings show that increasing concentrations of serum of LHCN‐M2 skeletal muscle cells into multinucleated myotubes, but this does not affect relative mitochondrial function.